Crafts for rural employment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Rural people have long shown their varied artistic talents as painters, potters, sculptors, carvers and weavers. Whether for family use, for barter or for sale, the production of artifacts has generally been regarded as a 'spare time' activity....